Hubungan Pengetahuan Ibu Hamil Terhadap Perilaku Kesehatan Gigi Dan Mulut Di Puskesmas Rancaekek DTP - Erni, Nani; Octaviana, Devy; Praptiwi, Yenny Hendriani; Supriyanto, Irwan (Poltekkes Kemenkes Bandung, 2024)
Pregnancy brings many changes to pregnant women. Pregnant women, if not handled properly, can have a negative impact on the health of the mother and baby, especially on the health of the oral cavity. Unkempt teeth contain harmful bacteria. These bacteria are toxins that easily enter the genital tract through the blood vessels and a bacterial infection occurs which causes inflammation in the uterine tract and can attack the unborn fetus which has the risk that fetal growth and development can be inhibited and disrupted. This study aims to determine the relationship between the level of knowledge of pregnant women about oral health and their behavior during pregnancy. This type of research is quantitative through a Cross Sectional research design, namely conducting research at the same time to connect the independent variables and the dependent variables studied on the sample and the specified population. The sample amounted to 41 respondents of pregnant women in the first, second and third trimester. This research was conducted at the Rancaekek Health Center DTP Bandung Regency in January - March 2024. This study used instruments in the form of questionnaires of Knowledge Level and Behavior. Data analysis used was Chi-Square (chi square <0.05). The results of this study found that there was a significant relationship between the level of knowledge and the oral health behavior of pregnant women during pregnancy. This can be caused by pregnant women who have knowledge related to oral health, and they apply it in their daily lives (already maintaining oral health during pregnancy according to their knowledge).